2007
DOI: 10.2967/jnumed.108.007369
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acquisition Geometry, Image Processing, and Patient Size on Lesion Detection in Whole-Body 18F-FDG PET

Abstract: The aim of this work was to develop a rigorous evaluation methodology to assess performance of different acquisition and processing methods for variable patient sizes in the context of lesion detection in whole-body 18 F-FDG PET. Methods: Fifty-nine bed positions were acquired in 32 patients in 2-dimensional (2D) and 3-dimensional (3D) modes 1-4 h after 18 F-FDG injection (740 MBq) using a BGO PET scanner. Three spheres (1.0-, 1.3-, and 1.6-cm diameter) containing 68 Ge were also imaged separately in air, at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 19 publications
(27 reference statements)
0
24
0
Order By: Relevance
“…This study did not take the subject size into consideration. However, the PET image quality of overweight subjects (body mass index $ 25) is degraded because of an increase in statistical noise (29)(30)(31). To obtain sufficient image quality, adjusting the injection activity or scanning time in each patient based on body weight or body mass index (29,32,33) might be required for overweight subjects (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…This study did not take the subject size into consideration. However, the PET image quality of overweight subjects (body mass index $ 25) is degraded because of an increase in statistical noise (29)(30)(31). To obtain sufficient image quality, adjusting the injection activity or scanning time in each patient based on body weight or body mass index (29,32,33) might be required for overweight subjects (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…In the visual evaluation, the influence of the local statistical noise due to attenuation was more significant in 3D mode than in 2D mode. A previous study also reported that a larger body mass index affected the detectability of lesions more significantly in 3D mode than in 2D mode [20]. This suggests that the adjustment of acquisition time would be more important in 3D mode than in 2D mode.…”
Section: Discussionmentioning
confidence: 85%
“…Adding simulated targets to real images (creating socalled hybrid images) becomes an interesting realistic option for task-based assessment studies. 16,24,25,64 Hence, image fusion between the simulated plaque features and patient's background demonstrated in our framework may be appropriately applied in clinical validation. This simulation work, which is a pilot study for the assessment of spectral CT in plaque imaging, can be applied to other clinical applications, such as coronary artery plaque imaging, differentiation of kidney stones, 65 or identification of gouty tophi.…”
Section: Dect-sw J=2mentioning
confidence: 99%
“…As a result, they are usually selected as a common metric for objective evaluation and comparison of medical imaging systems. 17,20,[22][23][24][25][26][27] Objective image assessment of the performance improvement obtained using spectral CT is mainly limited to investigation of particular clinical tasks. Several studies have shown that material decomposition with spectral CT imaging provides better differentiation of materials for atherosclerotic plaque features.…”
Section: Introductionmentioning
confidence: 99%